Estrategias de ventas en el Comercial Escobar de la ciudad de Vinces, durante el período 2023. - Plaza Carranza, Germania Gisella (2024)
This case study focused on analyzing Comercial Escobar's sales strategy in the province of Vinces, with the aim of improving its competitiveness and market positioning. The analysis began by identifying the problem of falling sales due to the lack of innovative strategies and the growing competition in the sector. Specific objectives were derived from this to understand the market needs, evaluate the strengths and weaknesses of the current sales model and propose strategic solutions. A quantitative study was carried out by surveying 382 people as a result of the sample that was carried out. The results show that food is the most in-demand product, while special offers and loyalty programs are perceived as essential elements to attract customers. In addition, there is a growing trend towards the digitalization of purchases. Based on this data, a swot analysis was carried out, highlighting strengths such as local knowledge and weaknesses such as the lack of digital channels. In addition, opportunities and risks related to the market and competition were also identified. As a result, strategies such as implementing targeted promotions, developing loyalty programs, and introducing digital distribution were proposed to meet market needs and address weaknesses. The final conclusions and recommendations highlight the importance of adopting innovative approaches to improve competitiveness and ensure sustainable business growth.